2019
DOI: 10.14238/pi59.2.2019.79-86
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference, body mass index, and skinfold thickness as potential risk factors for high blood pressure in adolescents

Abstract: Background The prevalence of hypertension in children and adolescents has increased with the rising obesity epidemic. Recent studies have found that prevalence of hypertension was higher in obese children or adolescents than in the normal weight ones. Anthropometric measurements such as body mass index (BMI), waist circumference, and skinfold thickness have been used as criteria to determine obesity in children and adolescents. Increased waist circumference has been most closely related to increased blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…(2019) revealed that abdominal circumference is the strongest predictive factor for increased systolic blood pressure, while BMI and skinfold triceps are predictive factors for increased diastolic blood pressure. 19 The same goes for a study by Kuciene et al (2019) that concluded that BMI is better as a predictor of hypertension than the ratio of abdominal circumference and height. Further research is needed to control these factors.…”
Section: Discussionmentioning
confidence: 73%
“…(2019) revealed that abdominal circumference is the strongest predictive factor for increased systolic blood pressure, while BMI and skinfold triceps are predictive factors for increased diastolic blood pressure. 19 The same goes for a study by Kuciene et al (2019) that concluded that BMI is better as a predictor of hypertension than the ratio of abdominal circumference and height. Further research is needed to control these factors.…”
Section: Discussionmentioning
confidence: 73%
“…4 and 5 shows two causal relationships with a change in direction: and . Between them, indicates that the change in BMI results in a change in the skin fold thickness of triceps (subcutaneous fat thickness).Studies have shown [ 32 , 33 ] that there is a significant correlation between the thickness of the triceps skin fold and BMI. When the BMI value increases, the weight change increases, and the subcutaneous fat thickness increases, so the causality is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…15 One of the predictive factor for elevated systolic blood pressure is waist circumference. 16 Waist circumference is also associated in hypertension incident. 17 Setyanda (2015) said that people who have a high WC measure are more at risk of developing hypertension, although WC does not directly affect the occurrence of hypertension.…”
Section: Discussionmentioning
confidence: 99%